2020
DOI: 10.1089/neu.2019.6631
|View full text |Cite
|
Sign up to set email alerts
|

Signal Information Prediction of Mortality Identifies Unique Patient Subsets after Severe Traumatic Brain Injury: A Decision-Tree Analysis Approach

Abstract: Nonlinear physiological signal features that reveal information content and causal flow have recently been shown to be predictors of mortality after severe traumatic brain injury (TBI). The extent to which these features interact together, and with traditional measures to describe patients in a clinically meaningful way remains unclear. In this study, we incorporated basic demographics (age and initial Glasgow coma scale, GCS) with linear and nonlinear signal information based features-approximate entropy (ApE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…In fact, complex temporal patterns including fractal patterns have been observed in many physiological signals 7–9 such as gait, 10 mobility, 11 motor function, 12 and activity patterns, 4,5 all of which have been linked to AD and pathology 13–16 . It has been accepted that fractal patterns are generated by multiple such processes in an ongoing feedback loop 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In fact, complex temporal patterns including fractal patterns have been observed in many physiological signals 7–9 such as gait, 10 mobility, 11 motor function, 12 and activity patterns, 4,5 all of which have been linked to AD and pathology 13–16 . It has been accepted that fractal patterns are generated by multiple such processes in an ongoing feedback loop 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The study concluded that age, Glasgow Coma Scale, fibrin/fibrinogen degradation products, and blood glucose were the most predictive factors of mortality amongst both TBI and elderly patients [22] . Abnormalities in these predictive criteria have been associated with inferior outcomes [23] , [24] . In this study, those who survived had significantly higher GCS scores (8.25 vs 5.63, P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with lower CGS scores tend to have poorer neurologic exams. While the strengths of GCS include its ease to measure and reliability, the use of GCS is limited in sedated patients, patients intoxicated with alcohol or drugs, and patients with facial fractures [24] . Both IMPACT and CRASH models demonstrate the prognostic value in predicting mortality within two weeks and unfavorable outcomes utilizing factors such as GCS, pupil response, age, hypoxia, glucose, and even hypotension [25] .…”
Section: Discussionmentioning
confidence: 99%
“…The majority of this cohort were elderly women due to the age group and voluntary nature of participation; this limits generalizability to a more general or younger population. Quantitative methods have recently been sought to best characterize physiological data, [30][31][32][33][34] including sleep behaviour. 35,36 The challenge has always been to extract meaningful and physiologically relevant insight into the underlying biological trait of interest.…”
Section: Discussionmentioning
confidence: 99%